Decolonising the Academy - Nyamnjoh, Francis B., 1961- (Book collections on Project MUSE., 2020)
"The scarcity of conviviality in universities, within and between disciplines, and among scholars suggests that the position in and production and consumption of knowledge are far from neutral, objective, and disinterested processes. They are socially and politically mediated by webs of humanity, hierarchies of power, and instances of human agency. Given the resilience of colonial education in Africa and among Africans, endogenous traditions of knowledge are barely recognised and grossly underrepresented. Conviviality in knowledge production would entail not just seeking conversations and collaboration with and across disciplines in the conventional sense but also the integration of sidestepped popular epistemologies informed by popular universes and ideas of reality. Such scholarship is predicated upon recognising and providing for incompleteness as a necessary attribute of being, from persons to disciplines and traditions of knowing, and knowledge making."